Heart failure with preserved ejection fraction, atrial fibrillation, and the role of senile amyloidosis. (8th February 2019) - van den Berg, Maarten P; Mulder, Bart A; Klaassen, Sebastiaan H C; Maass, Alexander H; van Veldhuisen, Dirk J; van der Meer, Peter; Nienhuis, Hans L A; Hazenberg, Bouke P C; Rienstra, Michiel
Abstract: Heart failure with preserved ejection fraction (HFpEF) and atrial fibrillation (AF) are very common conditions, particularly in the elderly. However, the mechanisms underlying the two disorders, including their intricate interaction have not been fully resolved. Here, our aim is to review the evidence on the role of the two types of senile amyloidosis in this connection. Two types of senile amyloidosis can be identified: wild-type transthyretin (TTR)-derived amyloidosis (ATTRwt) and isolated atrial amyloidosis (IAA). ATTRwt is an underlying condition that is being increasingly recognized in patients with HFpEF and often accompanied by AF. IAA is an established cause of AF, adding to the mechanism problem. New diagnostic and therapeutic possibilities have emerged that may facilitate clinical management of (senile) amyloidosis, which in turn may have implications for the management of HFpEF and AF.